Development of high-volume recycled glass ultra-high-performance concrete with high C3A cement - Jesús D. Redondo-Mosquera; David Sánchez-Angarita; Marcela Redondo-Pérez; Juan C. Gómez-Espitia; Joaquín Abellán-García (Case Studies in Construction Materials, 2023)
Ultra-high-performance concrete (UHPC) is a special cementitious composite material with outstanding qualities like compressive strength greater than 120 MPa, and outstanding durability in comparison to other types of concrete. However, its production implies a large carbon footprint and significant consumption of natural resources such as quartz powder and fine quartz sand, both classified as carcinogenic to humans by the International Agency for Research on Cancer. This study produced a UHPC paste created with greener pozzolans and aggregates compared to current UHPC mixture proportions. In this regard, quartz powder and fine quartz sand were replaced by two different sizes of recycled glass powder. Furthermore, reducing the cement dosage was a goal in optimizing the UHPC mixture. This total replacement of the aggregate and reduction of the cement reduces the carbon footprint and the costs of the final material in two different ways: firstly, by decreasing the use of natural resources to produce quartz powder and sand, and secondly, by using waste material that otherwise would occupy landfill space. To reproduce the findings of this paper in developing countries with limited-quality cement, high C3A locally available cement is used in this research. The latter represents a significant challenge in the production of UHPC. Statistical methodologies such as center composite design and multiobjective optimization were undertaken to develop an efficient, healthy, safe, and environmentally friendly mixture design that meets the ASTM strength criteria for UHPC while maintaining the lowest cement content and the highest waste material dosage. The results showed that the fact that all the ground recycled glass particles have a size of less than 1 mm is not a sufficient condition to avoid the harmful alkali-silica reaction. In addition, it was observed that the high C3A content of the locally available cement had a slight positive effect on the 1-day compressive strength but a significant negative effect on the 28-day compressive strength of the UHPC. Finally, the present investigation demonstrated the feasibility of producing a UHPC that, using a local cement with almost 10% C3A, met the threshold criteria with a large volume use of recycled glass powder representing more than fifty percent by weight of total concrete.